Editors’ introduction: Cynthia Ozick and the art of nonfiction - Mendelssohn, M; Tyson, C (Pennsylvania State University Press, 2024)
A 2016 New York Times profile of Cynthia Ozick summarized her career in the following terms: This special issue of Studies in American Jewish Literature focuses on Ozick’s essays, criticism, reviews, memoiristic pieces, and certain unclassifiable hybrids, fragments, and thought experiments—the productions, as it were, of the other hand. It aims to take the measure of this ambidextrous author through her nonfiction, while keeping in mind the awkwardness of this category for a writer whose essays frequently display a defiant blurring of the fictive and the factual. From her home in New Rochelle, Ozick has over the decades quietly produced one of the major bodies of literary essays in contemporary American letters. Her essays are vivid and mannered productions. Much of their interest resides in the linguistic virtuosity with which Ozick gives voice to attachments and aversions that some readers may find bewilderingly fierce. And then there is her magnificent...